Respostas

  • PeH
  • Ambicioso
2013-04-27T12:21:49-03:00

A raiz de uma função é obtida igualando-a a zero:

 

\blacktriangleright a) \ x + 8 = 0

 

x = -8

 

 

\blacktriangleright b) \ 2x - 4 = 0

 

2x = 4

 

x = \frac{4}{2}

 

x = 2

 

 

\blacktriangleright c) -3x + 18 = 0

 

-3x = -18

 

x = \frac{-18}{-3}

 

x = 6

 

 

\blacktriangleright d) \ \frac{3}{2}x - 6 = 0

 

\frac{3}{2}x = 6

 

x = 6 : \frac{3}{2} = 6 \cdot \frac{2}{3} = \frac{12}{3}

 

x = \frac{12}{3} = 4

 

 

5 4 5